Effect Of Final Irrigation Materials And Techniques On Sealer Penetration Depth Into Dentinal Tubule Of The Apical Third Root Canal - Premadhika, Yogi; Ratih, Diatri Nari; Widyastuti, Andina (Odonto : Dental Journal, 2024)
Background: The smear layer may interfere with the penetration of the root canal sealer. Final irrigation is known to improve chelating agents' ability in smear layer removal. This study aimed to compare the effect of various materials and final irrigation techniques on the penetration depth of bioceramic silers in the apical third of the tooth.Method: This study used 45 premolars that were prepared with a rotary instrument and then randomly divided into three experimental groups (n=15). Group 1 used 17% EDTA as the final irrigation material, group 2 used Novel Silver Citrate, and group 3 used 0.2% nanoparticle chitosan. Each group was divided into three subgroups (n=5), with subgroup A using manual agitation technique, subgroup B using sonic agitation, and subgroup C using ultrasonic agitation. The teeth were then obturated using a bioceramic sealer. Teeth then cut vertically for observation and measurement  sealer penetration using a stereo microscope with a magnification of 30x followed by observation using SEM at 1000x magnification. data where analyzed using a two-way ANOVA followed by an LSD Post Hoc test, with a significance level of 95%.Result: Two-way ANOVA showed significant differences in materials, techniques, and material-technique interactions (p<0,05).Conclusion: This study concludes that there is an effect of material, technique, and material-technique interaction of final irrigation on the penetration of bioceramic sealer into the dentinal tubules, Combination of 0.2% chitosan nanoparticles and sonic agitation as material and final irrigation technique resulted in the most longest penetration of bioceramic sealer into dentinal tubules.